Impaction of lower third molars and their association with age: radiological perspectives - Soukaina Ryalat; Saif Aldeen AlRyalat; Zaid Kassob; Yazan Hassona; Mohammad H. Al-Shayyab; Faleh Sawair (BMC, 2018)
Abstract Background Third molars are the most commonly impacted teeth, and their extraction is the most commonly performed procedure in oral and maxillofacial surgery. The aim of the present study is to describe the pattern of mandibular third molar impaction and to define the most appropriate age for prophylactic extraction of mandibular third molar teeth. Methods A total of 1198 orthopantomographs (OPGs) with 1810 impacted lower third molars were reviewed by two authors. The pattern of eruption in relation to patient's age was examined using standard radiographic points and angles. Statistical analysis was performed using SPSS for Windows release 16.0 (SPSS Inc., Chicago, IL, USA). Results In patients older than 20 years, vertical pattern of impaction was the most common (21.4%); while in young patients; horizontal impaction was more common (21.3%). Furthermore, there was a constant pattern of increase in Pell-Gregory ramus class 1 with increasing age, as the prevalence of class 1 was 0% at age 18 years compared to 54.9% at the age of 26 years. Conclusion Frequency of vertical impaction of lower third molars was seen more at an older age (> 20 years) in this study, with an increase in the retromolar space. Late extraction of mandibular third molar teeth (i.e. after the age of 20) is therefore recommended when prophylactic extraction is considered.